2022
DOI: 10.3389/fcvm.2022.1074956
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of right ventricular longitudinal shortening fraction assessed by transthoracic and transoesophageal echocardiography in the perioperative setting: A prospective study

Abstract: BackgroundConventional transthoracic (TTE) and transoesophageal echocardiography (TEE) parameters assessing right ventricle (RV) systolic function are daily used assuming their clinical interchangeability. RV longitudinal shortening fraction (RV-LSF) is a two-dimensional speckle tracking parameter used to assess RV systolic function. RV-LSF is based on tricuspid annular displacement analysis and could be measured with TTE or TEE.ObjectiveThe aim of the study was to determine if RV-LSFTTE and RV-LSFTEE measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Second, further research is also needed to confirm the prognostic value of STE strain parameters in such a population, as the number of studies focusing on this was relatively small. Third, the primary limitation of STE strain analysis is its intrinsic requirement for good picture quality, which has not been adequately addressed thus far [ 71 , 72 , 73 , 74 , 75 ]. Additional research is necessary to maximize its clinical application.…”
Section: Current Limitations and Future Prospectsmentioning
confidence: 99%
“…Second, further research is also needed to confirm the prognostic value of STE strain parameters in such a population, as the number of studies focusing on this was relatively small. Third, the primary limitation of STE strain analysis is its intrinsic requirement for good picture quality, which has not been adequately addressed thus far [ 71 , 72 , 73 , 74 , 75 ]. Additional research is necessary to maximize its clinical application.…”
Section: Current Limitations and Future Prospectsmentioning
confidence: 99%
“…Although the EACVI/ASE Joint Task Force recommendations emphasize analysis in the RV-focused four-chamber view ( 15 ), studies have demonstrated that RV strain values from subcostal views are highly correlated with those from the apical view (Pearson's r = 0.89) in 94 cases with veno-venous (V-V) ECMO ( 50 ). RV strain values from the four-chamber view using transesophageal echocardiography also showed a high correlation with those from the RV-focused four-chamber view using transthoracic echocardiography ( r = 0.9; 95% CI 0.87–0.94) ( 51 ).…”
Section: Manuscriptmentioning
confidence: 99%